Unique pharmacological properties of serotoninergic G-protein coupled receptors from cestodes. - Federico Camicia; Ana M Celentano; Malcolm E Johns; John D Chan; Lucas Maldonado; Hugo Vaca; Nicolás Di Siervi; Laura Kamentezky; Ana M Gamo; Silvia Ortega-Gutierrez; Mar Martin-Fontecha; Carlos Davio; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Cestodes are a diverse group of parasites, some of them being agents of neglected diseases. In cestodes, little is known about the functional properties of G protein coupled receptors (GPCRs) which have proved to be highly druggable targets in other organisms. Notably, serotoninergic G-protein coupled receptors (5-HT GPCRs) play major roles in key functions like movement, development and reproduction in parasites. METHODOLOGY/PRINCIPAL FINDINGS:Three 5-HT GPCRs from Echinococcus granulosus and Mesocestoides corti were cloned, sequenced, bioinformatically analyzed and functionally characterized. Multiple sequence alignment with other GPCRs showed the presence of seven transmembrane segments and conserved motifs but interesting differences were also observed. Phylogenetic analysis grouped these new sequences within the 5-HT7 clade of GPCRs. Molecular modeling showed a striking resemblance in the spatial localization of key residues with their mammalian counterparts. Expression analysis using available RNAseq data showed that both E. granulosus sequences are expressed in larval and adult stages. Localization studies performed in E. granulosus larvae with a fluorescent probe produced a punctiform pattern concentrated in suckers. E. granulosus and M. corti larvae showed an increase in motility in response to serotonin. Heterologous expression revealed elevated levels of cAMP production in response to 5-HT and two of the GPCRs showed extremely high sensitivity to 5-HT (picomolar range). While each of these GPCRs was activated by 5-HT, they exhibit distinct pharmacological properties (5-HT sensitivity, differential responsiveness to ligands). CONCLUSIONS/SIGNIFICANCE:These data provide the first functional report of GPCRs in parasitic cestodes. The serotoninergic GPCRs characterized here may represent novel druggable targets for antiparasitic intervention.